Reconstruction of the cervical ligament in patients with chronic subtalar instability. Issue 8 (December 2022) - Michels, Frederick; Stockmans, Filip; Pottel, Hans; Matricali, Giovanni
Abstract: Purpose: Diagnosis and treatment of subtalar instability (STI) remains complicated and challenging. The purpose of this study was to investigate the outcome of an anatomical reconstruction of the cervical ligament in patients with suspected chronic STI. Methods: This prospective study assessed the results of a surgical reconstruction of the cervical ligament using a gracilis tendon graft in a group of 14 patients (16 feet). Diagnosis of STI was performed using a predefined algorithm including clinical signs, MRI and peroperative evaluation. All patients had symptoms of chronic hindfoot instability despite prolonged non-surgical treatment. At final follow-up the outcome was assessed using the Karlsson score, the Foot and Ankle Outcome Score and the American Orthopaedic Foot and Ankle Society score. Results: After an average follow up of 22.6 months (range, 15–36), all patients reported significant improvement compared to their preoperative symptoms. The mean preoperative Karlsson score improved from 36.4 ± 13.5 (median 37, range 10–55) to a mean postoperative Karlsson score was 89.6 ± 8.5 (median 90, range 72–100) (P < 0.0001). The cervical ligament reconstruction was combined with other procedures in 13 cases: calcaneofibular ligament (CFL) reconstruction (3), CFL and anterior talofibular ligament reconstruction (7), bifurcate ligament reconstruction (3). Conclusion: Anatomical reconstruction of the cervical ligament is a valid technique to treat patients with STI. It is a safe procedure and produces good clinical results with minimal complications. This technique can be considered in more complex cases and can be combined with other procedures according to the specific location of the instability. Level of evidence: Level III Highlights: Anatomical reconstruction of the cervical ligament is a valid technique to treat patients with subtalar instability. Patient selection can be performed by an algorithm including clinical signs, MRI and peroperative evaluation. Cervical ligament reconstruction can be considered in more complex cases of hindfoot instability. Cervical ligament reconstruction can be performed as an isolated procedure of in combination with other procedures.